PERAN KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA DISIPLIN DI MTsN 2 KOTA PADANG - Linsi Efsya Putri; Awida Awida (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2023)
This article is motivated by the role of the madrasa head in developing a culture of discipline at MTsN 2 Padang City. This study aims to find out what actions are taken to discipline it, this can be seen by symptoms such as students who arrive late, students who are late for more than 15 minutes are told to go home, there are still students who are not dressed neatly, there are students who play in the madrasa yard during class hours, there are still students who don't do homework. The results of the findings of the madrasa principal's strategy in developing a discipline culture in the field of discipline, first, the discipline in the madrasa is discussed every year to further refine it. So, this is a pretty good thing. This means that the discipline of students in this madrasa is always being improved. in compiling the rules, the madrasah also invited parents of students, teachers, head of the madrasah, TU staff. this is a good thing, because by involving the student's guardians in the preparation of the rules, the student's guardians will automatically know what rules apply in the madrasa. Second, after the rules have been discussed and approved, then the head of the madrasa socializes the rules so that students know what obligations and restrictions apply. The socialization that was implemented was by explaining it during the school orientation period (MOS), displaying the rules of conduct in each class, the school principal, guidance counselor and other teachers always reminded students. This way of socialization should be effective enough to make students understand the culture of discipline in the madrasa.